Niepogoda dla secesjonistów. Przykład Jarosława Gowina - Olszanecka, Agata (Political Preferences, 2014)
The intra-party conflicts tend to be more common on Polish political scene in last few years. This kind of political competition was not avoided by the ruling party - Civic Platform. The conflict between Prime Minister Donald Tusk and former Minister of Justice Jarosław Gowin has escalated during the internal election in Civic Platform. Despite the Gowin's failure in party chairman election, he reached a substantial support among party members and electorate. After that, Gowin decided to leave Civic Platform and established his own political formation - Poland Together (PolskaRazem). Presented article is aimed at examining the perception of party leadership of Donald Tusk and the political potential of Jarosław Gowin. According to the research and this year's European Parliament election the author tried to answer the question whether Gowin's party can achieve the relevant position in Polish party system.